Yorkshire Lasses and their Lads: Sexuality, Sexual Customs, and Gender Antagonisms in Anglo-American Working-Class Culture. - Blewett, Mary (Journal of Social History)
The writer examines how Yorkshire lasses and older women used their sexuality to define their female adulthood through sexual experimentation during courtship, to discipline male aggressiveness and patriarchy, and to advance their status as working women. She asserts that Yorkshire working-class women's behavior and customs reveal how they confronted on their own terms both gender and class conflicts in the family, the workplace, and the trade union. She contends that the threatening power of female sexuality exercised collectively, openly, and dramatically reminded all that sexuality and the workplace were deeply connected but not always at the expense of women.